Comparative content analysis on news treatment of Manila Bulletin and Philippine Daily Inquirer on the demolition of houses of Metro Manila urban poor during the Ramos administration - Sanvictores, Benito Valencia, Jr. 1976-; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This study is a comparative content analysis of newspapers Manila Bulletin and Philippine Daily Inquirer regarding their treatment of news reports on the demolition of houses of Metro Manila urban poor during the Ramos Administration. The main objective of this study is to determine the priority the Bulletin and Inquirer give to reports on demolition. The theory used here was the Theory of Institutionalized Public Acculturation by George Gerbner. According to Gerbner, the public's perception of personalities, events, and institutions depends mainly on how the mass media portray these entities. The method used was the frequency distribution to be able to find out how much attention and emphasis (or the manifest content) was given to demolition reports. aside from the manifest content, the latent content (tendency and focus) of the articles was also determined. The results of this study showed that in terms of the manifest content, the Inquirer gave more attention and emphasis to reports on demolition of houses of the urban poor during the Ramos Administration. The Inquirer published a total of 29 articles compared to 9 articles of the Bulletin. This was affirmed by the computed Emphasis Score (ES) of both newspapers, wherein the Inquirer has a higher score than the Bulletin, in terms of page placement, headline size, cut area of article and the presence of photographs. In terms of tendency, the two newspapers portrayed the urban poor differently. In almost all of the Inquirer's reports, the urban poor was described as "victim," and the government "insincere" in upholding its promises. However, in the Bulletin they were almost always described as the "culprits' and the government earnestly doing all it could to solve the problem. The Inquirer focused on the themes that the demolitions were illegal, and the government and other concerned entities do not provide adequate and suitable relocation sites for the displaced squatter families, if there were any such relocation sites. On the other hand, the Bulletin focused on the themes that the urban poor was a "menace" to society, thus, preventing the progress in the metropolis, and that the government was doing everything to provide the urban poor with effective housing programs. The nature of the reports are contrasting in terms of the angles used. In the Inquirer, the urban poor was always on the losing end with their rights not protected, or at least honored. In the Bulletin, the poor was almost always at fault, and that if they would obey the authority, they would benefit from the housing program of the government.
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: Manila Bulletin -- Philippines -- News writing; Philippine Daily Inquirer -- Philippines -- News writing; Wrecking -- Philippines -- Houses